Regional Government Information System Program at the Regional Secretariat Bitung City - Mawuntu, Inriani Christy; Sendouw, Recky H E; Kairupan, Sisca Beatrix (International Journal of Information Technology and Education, 2024)
This study aims to (1) find out how SIPD is implemented in the Bitung City Regional Secretariat, especially in the Planning and Finance Section, and (2) find out and describe the implementation of SIPD in the Bitung City Regional Secretariat. This study uses a descriptive method with a qualitative approach, where what is collected is opinions, responses, information, concepts, and descriptions in the form of descriptions in expressing problems. Denzin and Lincoln (2021), qualitative research with descriptive methods now emphasizes more on the contextualization and localization of the phenomena being studied. Research not only aims to describe phenomena in general but also to understand how these phenomena play a role in certain local contexts. This is important to provide relevant and applicable insights for certain communities or regions. The results of the study show that the Implementation of the Regional Government Information System (SIPD) in the Bitung City Government has been running since 2021 following applicable regulations. Planning and organizing have been carried out well through training and technical assistance. However, there are still several obstacles, such as data input errors due to human error, limited SIPD application features, and inadequate internet networks and devices. The implementation of SIPD also faces obstacles in data input, which is often delayed due to application maintenance and a lack of routine training for new personnel. Supervision has been carried out through monthly meetings and monitoring based on communication groups, but its effectiveness still needs to be improved. To support more optimal implementation, routine training, improving infrastructure quality, and improvements to the SIPD application by the central government are needed to make it more stable and functional. This is important to ensure smooth planning, budgeting, and reporting following the objectives of the system.